Evaluation of Heat Shock Protein-90 as a Potential Risk Marker in Sera Women with Breast Cancer - Addai Ali, Hanaa; Mueen Hassoun, Safaa; Alkadhim Abd, Maha Abd; Saleh Mashkour, Muthana; Adday Ali, Rawaa; Kadhim Alyaseen, Mohammed (Asian Pacific Journal of Cancer Biology, 2025)
Background: Breast cancer (BC), the second most common kind of newly diagnosed malignancy worldwide, is the most common illness among women. Heat shock protein 90 (Hsp-90) is really important in the growth and dissemination of cancer cells by preserving the stability of overexpressed signaling proteins. Aim of study: Evaluate Hsp-90 serum levels as risk markers in breast cancer patients as compared to those in good health. Subject matter and methodology: The research included 180 participants. Ninety females with BC (23 stage I, 36 stage II, 24 stage III, and 7 stage IV) contrasted with 90 healthy women as a control group matched with patients in age. Serum heat shock protein-90 was measured using the ELISA technique kits. Additionally, lipid profiles and liver enzyme were assessed. Results: Serum Hsp-90 levels were significantly increased in all stages of women with BC compared to healthy women (P < 0.001) as well as between stages. There was an uptick in serum TC, ALT, ALP, TG, LDL-C, and VLDL-C levels in patients but lower serum HDL-C in those patients in comparison with healthy controls. Hsp-90 has a significant positive correlation with age, ALP, TG, TC, HDL-C, LDL-C, ALT, AST, and VLDL-C except BMI. Heat shock protein 90 showed good diagnostic efficiency in breast cancer patients, as the cut-off value of Hsp-90 (300.5 pg/mL) with sensitivity 88.9% and specificity 87.8% (AUC 0.907, 95% CI: 0.86-0.954; P < 0.001).